Diagram technique for the Hubbard model. Ladder diagram summation - Moskalenko, V.A.; Kon, L.Z. (Condensed Matter Physics, 1998)
A new diagram technique based on the generalized Wick theorem has
been elaborated for the systems with strong electronic correlations. Coulomb
repulsion of the electrons of the Hubbard model is considered as
the main part of Hamiltonian and is taken into account in a zero order approximation.
The hopping matrix elements are considered as a perturbation.
One-particle Matsubara-Green function of the model has been investigated
and Dyson equation has been obtained. New elements of the theory
which are characteristic of this new approach are the local many-particle
irreducible Green functions, or Kubo cumulants. They become zero when
Coulomb interaction is zero. The main task of this paper is the summing
of ladder diagrams which take into account the most essential charge and
spin fluctuations of the system. The integral equations, which sum such diagrams,
have been established for two different channels. The coherent potential
approximation has been used to simplify and solve these equations.
On this basis a metal-dielectric phase transition has been investigated. На основі узагальненої теореми Віка розроблено нову діаграмну техніку для систем з сильними електронними кореляціями. Кулонівське відштовхування електронів в моделі Хаббарда розглядається як головна частина гамільтоніана і враховується в нульовому наближенні. Матричний елемент міжвузлового перескоку електронів враховується як збурення. Досліджено одночастинкову мацубарівську функцію Гріна й отримано рівняння Дайсона. Новими елементами теорії, що характерні для даного наближення, є багаточастинкові незвідні функції Кубо. Вони обертаються в нуль, коли кулонівська взаємодія
рівна нулю. Головна мета даної роботи – це сумування драбинкових діаграм, що враховують найбільш суттєві спінові і зарядові флуктуації системи. Отримані інтегральні рівняння для двох каналів розсіяння.
Метод когерентного потенціалу використовується для спрощення і розв’язування цих рівнянь. На цій основі встановлена умова переходу метал-діелектрик.